**Q: Find the derivative of (x² – 5x + 2)*(x – 2/x)**

A: First, I am going to rewrite the problem:

(x² – 5x + 2)*(x – 2/x) = (x² – 5x + 2)*(x – 2x^{-1})

Now, we are going to apply the **product rule**. The product rule tells us how to take the derivative of a function times another function: f*g

The product rule says that the derivative of f*g is f ‘ * g + g ‘ * f

f = x² – 5x + 2 g = x – 2x^{-1}

f ‘ = 2x – 5 g’ = 1 + 2x^{-2}

^{So, plug the following in to f ‘ * g + g ‘ * f to get the answer:}

(2x – 5)(x – 2x^{-1}) + (1 + 2x^{-2})(x² – 5x + 2)

You could also reverse the order:

(1 + 2x^{-2})(x² – 5x + 2) + (2x – 5)(x – 2x^{-1})